DEVELOPMENT OF STUDENTS' CRITICAL THINKING DURING FOREIGN LANGUAGE CLASSES IN HIGHER EDUCATION INSTITUTION - Shcherbytska Vladyslava; Pysmenna Inna; Goliak Viktoriia (Alfred Nobel University Publisher, 2022)
The article talks about the need to develop critical thinking among students in general, and, in particular, considers the issue of developing critical thinking of students in foreign language classes, using the example of German language classes. It is emphasized that since the beginning of a full-scale war, this issue has gained considerable importance, because a critical way of thinking makes it possible to analyse the information received, make the right decisions, resist information pressure, and be tolerant of the opinions of opponents. The purpose of the article is to reveal the need for the development of critical thinking in students during foreign language classes in institutions of higher education, as well as to analyse the peculiarities of the implementation of some methods and forms of education that ensure the development of critical thinking in students during foreign language classes using the example of German language classes. The work uses both general scientific and linguistic research methods, namely: theoretical (analysis, synthesis and generalization of the latest research and publications); empirical (observation of the educational process); experimental (studying the results of students' activities). The article defines the concept of "critical thinking" and analyses the latest research and publications on this issue. Three stages of development of critical thinking are characterized: challenge, implementation, and reflection. The methods and forms of development of critical thinking are considered, namely: discussions, disputes, and debates, role-playing games, press conferences, talk shows, etc. Some of them are analysed. The role of the teacher in this process is emphasized. There are five rules of a creative teacher. An authentic textbook on the German language is offered, which, according to the authors, contributes to the development of critical thinking in students. Word games in German are offered, which also contribute to the development of critical thinking. It is noted that mastering the habit of critical thinking has many advantages, including a deep understanding of one's own values and needs, the ability to make quick decisions, the ability to resist information pressure (which is very powerful nowadays), as well as a tolerant attitude to the opinions of others. The successful implementation of critical thinking development technology during foreign language classes in institutions of higher education contributes to students' acquisition of skills and knowledge that go beyond the subject of a foreign language. Critical thinking gives not only comprehensive knowledge of a set of topics, but also forms a special worldview, helps to find out the causes of the origin of such knowledge, and forms the ability to predict consequences. During the practical use of this technology in German classes, we managed to activate the educational process, arouse students' interest in studying certain topics, and increase motivation. Students learned large volumes of information without boredom and fatigue due to the variety of tasks. In the conditions of joint creative work, partnership relations were formed between the students and the teacher. It is emphasized that the introduction of technology for the development of critical thinking will help students determine themselves in their personal, professional, and social life, and will increase their competitiveness in the global labour market.